Acoustic Properties of the Lake Sevan - Mkrtchyan, A. H.; Mkrtchyan, A. R.; Bagdasaryan, A. S.; Saryan, V. K.; Atanesyan, A. K.; Harutyunyan, G. A.; Mkhitaryan, S. A.; Kotanjyan, Kh. V.; Mirakyan, S. A.; Agabekyan, V. N.; Nalbandyan, V. V.; Muradyan, H. R.; et al.
The work is devoted to the studies of the acoustic properties of the Lake Sevan located on the territory of the Republic of Armenia. The dependences of acoustic properties on the underlying multilayered stratums structure and the form of the Lake Sevan were investigated. The characteristic background noise, the fundamental resonant frequencies and the coefficients of transmission of acoustic waves through layered structures with different orders of arrangements of the layers were found. Acoustic waves spread from artificial and natural sources were experimentally detected. The appropriate temporal and frequency spectra from different sources of acoustic waves were recorded. The phenomenon of reverberation of acoustic waves was registered. The measurements were conducted by means of specially developed unique registration systems of super week acoustic waves and vertical seismograph SM–3. Based on the comprehensive analyzes of the obtained experimental data and theoretical calculations, the utilization of the lakes and water cavities in areas with a certain geological structure as antennas and accumulating systems of super weak acoustic waves can be confirmed.
Keywords: Physics; Acoustics